Karakteristik Mekanik Komposit Poliester Berpenguat Serat Sisal Yang Diekstraksi Dengan Metode Water Retting Di Cetak Teknik Vacuum - Purwadi, Rafi; Surata, I Wayan; Nindhia, Tjokorda Gde Tirta (Teknik Desain Mekanika; Vol 10 No 3 (2021): Juli 2021 : Teknik Desain Mekanika, 2021)
Abstracta Composite isla material which is a combination of two or more different components, that is fiber as a filler and a matrix as a fiber binding material with the aim of obtaining certain better physical and mechanical properties to reduce the use of metal. The advantages of composites are light, strong, resistant to corrosion, low density, low price and good mechanical properties. Research to make composites with natural fiber reinforcement is expected to increase the use of metals. In this study, sisal fiber was extracted using the water retting method using a Yukalac 157 BQTN polyester matrix with a 1% MEKPO catalyst mixture. Where the sisal fiber was treated with 5% NaOH for 2 hours. The composite fusion stage uses a vacuum technique with variations in fiber weight fraction: 0%, 1%, 2%, 3% and 4% with random fiber orientation. The composite cuts followed the standards of ASTM D 638 for the Tensile test and ASTM D790-03 for the flexural test.The highest tensile strength of the composite was found in the 0% fiberless fraction with an average tensile stress value of 33.33 Mpa. Then it decreases with increasing fiber weight fraction to 4% with the lowest tensile strength of 12.76 Mpa. While the highest flexural strength is found in the 0% fiberless fraction with an average flexural stress valueaofk102.68 Mpa. while the lowest flexural stress is found in the 4% fiber weight fraction of 37.32 Mpa. Keywords6: sisal fiber, single fiber,btensilesstrength, flexural strength.